Development and evolution of clinical partnerships: K-12 school leaders' perspectives - Kimberly Bohannon; Vincent Connelly; Stephen Bigaj; Laura M. Wasielewski (Emerald Publishing, 2024)
Purpose - The purpose of this research study was to examine school leaders' critical perspectives about the nature of their partnerships with K-12 schools and two Educator Preparation Programs (EPP). Design/methodology/approach - Data were collected through interviews with K-12 school leaders to obtain partners' critical perspectives about school-EPP partnerships. The interviews were coded thematically and oriented around the central concept of working to represent the interplay of the participants and their collaborators' perceptions of the nature and dimensions of school-EPP partnerships. Findings - The analysis resulted in the construction of a mosaic of school leaders' collective lived experiences using a statewide conceptual framework as a guide. Four themes emerged from our interviews with school partners: (a) the need for dynamic, responsive and synergistic partnerships; (b) the need to monitor and maintain the underlying structure and integrity of the partnership; (c) the culture of interns as colleagues or as visitors; and (d) the need to innovate. Originality/value - Four themes emerged from our interviews with school partners: (1) the need for dynamic, responsive and synergistic partnerships; (2) the need to monitor and maintain the underlying structure and integrity of partnerships; (3) the culture of interns as colleagues or interns as visitors; and (4) the need to innovate.